Collection methods to preserve nutritive and physicochemical properties of unfermented coconut (Cocos nucifera) sap - Pathirana, Dilani Thilanka Hewa; Wijesekara, Isuru; Yalegama, L. L. W. C.; Jayasinghe, M. A. (International Coconut Community Journal, 2023)
Quality evaluation of unfermented coconut (Cocosnucifera) sap was done using two sap collection methods of application of Hal bark (Vateria acuminate) to the clay pots of 4L (TM) and novel sap collection method (NSCM), during 12 hours (from 6pm to 6 am). The novel sap collecting device is a recent innovation by Coconut Research Institute(CRI) – Sri Lanka. Twelve tapped coconut palms (Dwraft variety, 45 years old) were used and filtered sap was stored (-18oC). Volume, pH, total soluble solids, alcohol content, total acidity, color, sugar profile, total phenols, EC50, Ascorbic acid content and mineral in two types of unfermented coconut sap samples were determined. The results revealed that coconut sap collected from NSCM has significantly high pH (5.99), moisture (83.20%), sucrose (13.71%), total sugar (19.99%) compared to the collected sap from TM. In contrast, the sap of TM method were significantly rich with total phenolic (65.90 mgGAE/100ml), EC50 (143.03 mg/ml), AEAC (0.2568 mg Vit C in 1g sample), browning index (6.76) and yellowing index (15.92). Moreover, Ca (39.3mg/L), Fe (3.08mg/L), Mn (0.96mg/L), Sr (0.14mg/L) Ba (0.33mg/L) were significantly high in TM. Hence, the novel sap collection method can be concluded as the best approach for collecting quality unfermented coconut sap with its natural quality.